Near Future Energy Crisis in Turkey and New Opportunities: Wind Energy - Onel, I. Y.; Aycicek, E.; Ozeira, S. (IEEE, 2009)
This study pays attention about near future energy bottleneck possibility in Turkey and investigates that the wind energy, is able to help solving this problem or not. At the beginning, energy supply and consumption trends are described in Turkey and then, the electricity infrastructure and running power plants information are given. After that, wind energy potential and operating wind farms in Turkey are mentioned. Next part of the study tells the legal arrangements and incitement mechanisms about renewable energy in Turkey. A financial analysis for 55MW site in Turkey and discussion about feasibility of the project are given at the end of the paper.
Keywords: Electricity market; feasibility; wind energy; wind power plant; Engineering